2015
DOI: 10.1007/s11095-015-1667-5
|View full text |Cite
|
Sign up to set email alerts
|

Local Sustained Delivery of 25-Hydroxyvitamin D3 for Production of Antimicrobial Peptides

Abstract: Purpose-This study seeks to develop fiber membranes for local sustained delivery of 25-hydroxyvitamin D 3 to induce the expression and secretion of LL-37 at or near the surgical site, which provides a novel therapeutic approach to minimize the risk of infections.Methods-25-hydroxyvitamin D 3 loaded poly( L -lactide) (PLA) and poly(ε-caprolactone) (PCL) fibers were produced by electrospinning. The morphology of obtained fibers was characterized using atomic force microscope (AFM) and scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
(44 reference statements)
1
21
0
Order By: Relevance
“…Thus, it could be speculated that the more important the role a cell played in immune defense, the more active the vitamin D pathway was present in the cell, and the more hCAP‐18/LL‐37 was generated, indicating the role of the vitamin D pathway in immune defense. Other evidence also supported this hypothesis in two studies . If either the human keratinocyte cell line (Hacat) or the human monocyte cell line (U937) were treated with 25‐(OH)VD for 5 days, the generation of LL‐37 by U937 (20 to 60 ng/mg) was about 10 times higher than that by Hacat (3 to 5 ng/mg) .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Thus, it could be speculated that the more important the role a cell played in immune defense, the more active the vitamin D pathway was present in the cell, and the more hCAP‐18/LL‐37 was generated, indicating the role of the vitamin D pathway in immune defense. Other evidence also supported this hypothesis in two studies . If either the human keratinocyte cell line (Hacat) or the human monocyte cell line (U937) were treated with 25‐(OH)VD for 5 days, the generation of LL‐37 by U937 (20 to 60 ng/mg) was about 10 times higher than that by Hacat (3 to 5 ng/mg) .…”
Section: Discussionmentioning
confidence: 79%
“…Other evidence also supported this hypothesis in two studies . If either the human keratinocyte cell line (Hacat) or the human monocyte cell line (U937) were treated with 25‐(OH)VD for 5 days, the generation of LL‐37 by U937 (20 to 60 ng/mg) was about 10 times higher than that by Hacat (3 to 5 ng/mg) . In addition, it was reported that the LL‐37 concentration was approximately 400 pg/mL in the supernatant of epidermal keratinocytes, which was approximately 5 to 10 times higher than the concentrations of LL‐37 in cell supernatants of hGFs and hPDLCs in the present study.…”
Section: Discussionmentioning
confidence: 79%
“…Our recent work demonstrated that the incorporation of 25D 3 in electrospun nanofiber membranes could induce endogenous expression of the antimicrobial peptide, LL-37 [22]. To further analyze the induction of antimicrobial peptides, this study developed a method to coencapsulate 25D 3 and pam3CSK4 peptide into nanofiber sutures.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study, we demonstrated for the first time that incorporation of 25D 3 into poly(εcaprolactone) (PCL) and poly(L-lactic acid) (PLA) fibers via electrospinning allowed sustained release over a period of 4 weeks, and the coculture of 25D 3 loaded PCL fibers with keratinocytes and monocytes greatly boosted the endogenous LL-37 production compared with the free drug [22]. Based on the model in Figure 1, co-delivery of a TLR agonist (e.g., pam3CSK4 peptide) and 25D 3 could enhance CYP27B1 expression and promote the conversion from 25D 3 to 1,25D 3 , resulting in production of more LL-37 peptide.…”
mentioning
confidence: 99%
“…AFM scanning revealed the surfaces to have increasing roughness with increasing levels of multiwalled-CNTs. Poly(L-lactide) and poly(ε-caprolactone) (PCL) fibres loaded with 25-hydroxyvitamin D3 (an antibiotic precursor) have been electrospun and characterised by AFM and other techniques [100]. PCL fibres were smooth, but were rougher for poly(L-lactide), and more so after than encapsulation of the drug.…”
Section: Nanofibresmentioning
confidence: 99%